Analisis Penggunaan E-Commerce, Akses Pemodalan, dan Pengelolaan Keuangan Terhadap Peningkatan Pendapatan UMKM - Zamzam, Ayu Raudah; Juliati Nasution, Yenni Samri; Anggraini, Tuti (Ekonomi, Keuangan, Investasi dan Syariah (EKUITAS), 2025)
The use of e-commerce, access to funding, and financial management can affect the performance of MSMEs. This research aims to determine the effect of e-commerce, access to funding, and financial management on the increase in income of MSMEs in Pulo Brayan Kota sub-district. This research is associative with a quantitative approach. The study consists of three independent variables, namely e-commerce (X1), access to funding (X2), financial management (X3), and one dependent variable: increase in MSME income (Y). The population and research use saturated sampling. The data were analyzed using multiple linear regression with SPSS version 25. The results of the study indicate that the use of e-commerce, access to capital, and financial management have a positive and significant effect on increasing MSME income in Pulo Brayan Kota Village, both partially and simultaneously, with a contribution of 87.5%. The use of e-commerce has a positive effect of 0.320, access to capital by 0.629, and financial management by 0.583 on increasing income. This indicates that digitalization, capital support, and good financial management practices play a significant role in driving MSME income growth in the digital economy era.